Intestinal Parasitic Infections and Associated Risk Factors in Primary School Children in Isuikwuato Local Government Area, Abia State, Nigeria (Sahel Journal of Life Sciences FUDMA, 2025)
Intestinal parasitic infections remain a significant public health concern, affecting over 450 million individuals globally, with children being disproportionately impacted due to their higher vulnerability. A total of 385 children from three primary schools in Isuikwuato Local Government Area, Abia State, were studied to determine the prevalence of intestinal parasitic infection. The faecal samples were collected and analyzed using the formol-ether sedimentation concentration technique. A well-structured questionnaire was designed and pre-tested to collect demographic, socio-economic, and behavioral data. The overall prevalence was 11.69%, and the highest prevalence was recorded in Amaba Central School. Four intestinal parasites (Entamoeba histolytica, Ancylostoma duodenale, Ascaris lumbricoides, and Balantidium coli) were recovered, with E. histolytica being the most prevalent. Low-prevalence mixed infection was also recorded. Female pupils and the age group (12-14 years) had higher prevalence rates. Some socio-demographic factors, like parents’ marital status, occupation, source of water, and toilet type, wearing of footwear, washing of hands, disposing of household waste, and biting of fingernails, were highly significant, while picking food items from the floor, household size, household income, and educational background were not statistically significant in the study area. This study highlights the urgent need for public health intervention. Provision of water, sanitation, and health facilities (WASH), regular deworming, and public health education are needed in the area and schools to bring down the prevalence rate.